Atypical Mycobacterial Infection in A Diabetic Patient: A Case Report (BIRDEM Medical Journal, 2017)
Atypical mycobacteria are opportunistic, acid-fast and ubiquitous organisms. It is not uncommon in our society and is usually acquired from environmental sources like water and soil. Immunocompromised patients are prone to develop this infection. Many cases with similar and additional features have been reported in foreign literature. We describe one case of this infection along with review of literature. This is a 45 year old Bangladeshi diabetic woman, who was referred from department of general surgery for non- healing cutaneous abscess in the left lower abdomen. The patient underwent surgical drainage with empirical antibiotic coverage. But as the lesions were not healing she was referred to Dermatology. After having clinical suspicion, biopsy was taken and histological examination revealed tuberculoid granulomas and in tissue culture M.fortuitum was isolated. Although M.fortuitum was resistant to commonly used antitubercular drugs but it was found sensitive to amikacin, clarithromycin and ethambutol . Combination of these drugs later proved to be successful.Birdem Med J 2017; 7(1): 68-71